The Strategy of the Office of Archives and Library of the Mentawai Islands in the Development of Library Services to Increase Community's Reading Interest - Ponilala Ponilala; Desna Aromatica; Fatia Fatimah (Postgraduate School, Universitas Negeri Padang, 2022)
This article aims to look at the strategy of the office of archives and library of the Mentawai Islands Regency in developing library services to increase public interest in reading in the Mentawai Islands Regency. The strategy in this study uses a Strength, Weakness, Opportunity, and Threat (SWOT) analysis. The research method used in this research is descriptive research with a qualitative approach. The results of the research obtained indicate that several factors make the implementation and performance of policies on libraries in the Mentawai Islands Regency not run well, namely the limitations of competent human resources in the field of libraries owned by the office of archives and library of the Mentawai Islands Regency, facilities and infrastructure owned still inadequate due to the lack of APBD owned by the government, less than optimal communication and library promotion, the attitude of the people who still consider education to be not so important, and the economic condition of the community due to the COVID-19 pandemic affecting people's focus, causing people's interest in reading to be low.